Adjuvant potential of low dose all-trans retinoic acid during oral typhoid vaccination in Zambian men. (4th February 2014) - Lisulo, M M; Kapulu, M C; Banda, R; Sinkala, E; Kayamba, V; Sianongo, S; Kelly, P
Summary: There is an urgent need to identify ways of enhancing the mucosal immune response to oral vaccines. Rotavirus vaccine protection is much lower in Africa and Asia than in industrialized countries, and no oral vaccine has efficacy approaching the best systemic vaccines. All- trans retinoic acid (ATRA) up-regulates expression of α4β7 integrin and CCR9 on lymphocytes in laboratory animals, increasing their gut tropism. The aim of this study was to establish the feasibility of using ATRA as an oral adjuvant for oral typhoid vaccination. In order to establish that standard doses of oral ATRA can achieve serum concentrations greater than 10 nmol/l, we measured ATRA, 9- cis and 13- cis retinoic acid in serum of 14 male volunteers before and 3 h after 10 mg ATRA. We then evaluated the effect of 10 mg ATRA given 1 h before, and for 7 days following, oral typhoid vaccine in eight men, and in 24 men given various control interventions. We measured immunoglobulin (Ig)A directed against lipopolysaccharide (LPS)and protein preparations of vaccine antigens in whole gut lavage fluid (WGLF) and both IgA and IgG in serum, 1 day prior to vaccination and on day 14. Median [interquartile range (IQR)] Cmax was 26·2 (11·7–39·5) nmol/l, with no evidence of cumulation over 8 days. No adverse events were observed. Specific IgA responses to LPS ( P = 0·02) and protein ( P = 0·04) were enhanced in WGLF, but no effect was seen on IgA or IgG in serum. ATRA was well absorbed, well tolerated and may be a promising candidate oral adjuvant.